TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN PRODUK SUSU CAIR DALAM KEMASAN KOPERASI PETERNAKAN BANDUNG SELATAN (KPBS) DI KOTA BANDUNG - Meyka Yulita; Dyah Aring Hepiana Lestari; Dwi Haryono (Lampung University, 2014)
The objectives of this study are to analyze: the level of costumers satisfaction and costumers loyalty to the packaged liquid milk products of KPBS. The research was conducted in the largest distributors that supply liquid milk in KPBS packaging to costumers, at Pasundan street 165, Bandung. The number of respondents in this study are 100 respondents. The method of analysis used in this study are Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA) and pyramid loyalty. The results showed that the level of costumers satisfaction to the packaged liquid milk products of KPBS based on the analysis CSI was 78.8%, meant that overall costumers felt “satisfied”. Based on the IPA, the costumers evaluated that promotion attributes, attractive packaging design, nutritional value, and content of performance of pakaged milk were needed to be improved. The level of costumers loyalty in the packaged liquid dairy products based on the analysis pyramid of KPBS loyalty was mostly not loyal costumers, because the number of committed buyer was smaller than the number of switcher buyer. Key words: liquid milk, satisfaction and costumers loyalty